Clinical Pharmacogenetic Testing and Application: Laboratory Medicine Clinical Practice Guidelines - Kim, Sollip (Ann Lab Med, 2017)
Pharmacogenetic testing for clinical applications is steadily increasing. Correct and adequate use of pharmacogenetic tests is important to reduce unnecessary medical costs and adverse patient outcomes. This document contains recommended pharmacogenetic testing guidelines for clinical application, interpretation, and result reporting through a literature review and evidence-based expert opinions for the clinical pharmacogenetic testing covered by public medical insurance in Korea. This document aims to improve the utility of pharmacogenetic testing in routine clinical settings.